SINGLE CENTRE RANDOMISED PILOT STUDY OF TWO REGIMENS (30 MINS DAILY OR 30 MINS WEEKLY FOR 12 WEEKS) OF TRANSCUTANEOUS TIBIAL NERVE STIMULATION USING A NOVEL DEVICE FOR TREATING MULTIPLE SCLEROSIS-RELATED OVERACTIVE BLADDER SYMPTOMS. Issue 11 (14th October 2015) - Seth, Jai; Haslam, Collette; Gonzales, Gwen; Pakzad, Mahreen; Vashisht, Arvind; Elneil, Sohier; Sahai, Arun; Knowles, Charles; Tucker, Art; Panicker, Jalesh
Abstract : Introduction: Percutaneous tibial nerve stimulation (PTNS) is effective for managing multiple sclerosis (MS)-related overactive bladder (OAB) symptoms. However the need for weekly clinic visits restricts its use. The purpose of this study was to evaluate safety and efficacy of a novel, self-applying device for managing OAB symptoms. Study design, materials and methods: 48 patients reporting OAB (MS n=24, idiopathic n=24), were randomized (1:1) to either daily or weekly treatments for 12 weeks with geko™, a novel device stimulating the tibial nerve transcutaneously. Efficacy was assessed using validated questionnaires (ICIQ-OAB, ICIQLUTS-QoL) and bladder diaries filled at weeks 4, 8, and 12. Urinary neurotrophins (Nerve growth factor (NGF) and Brain derived neurotrophic factor) were measured. Results: 34 patients (MS n=19) completed the study. 18 patients responded to treatment (53%); 72% of responders belonged to the MS cohort. Multilevel regression analysis suggested significant improvements in questionnaire scores (ICIQ-OAB –10.2 (–13.5 to –6.9; p=0.001), ICIQLUTS-QOL –40.8 (–57.4 to –24.3; p=0.000)), without differences between weekly and daily-treated arms. No significant adverse effects were reported and patients rated the treatment as easy to use and comfortable. NGF levels at baseline were significantly greater in non-responders (p=0.05). Concluding message: In this pilot study, a patch device suitable for self-application at home appears to be an effective, safe and convenient alternative for managing MS-related OAB symptoms.